Environmental risks of biomass ashes application in soils [Resumo] - Freire, M. (2015)
This work presents the potential environmental risks of biomass ashes application in forest soils. The ashes were collected in five industrial biomass thermal plants using different technologies: bubbling fluidized bed combustor and grate furnace.